The Sonnet and its Travels. Issue 2 (August 2017) - Regan, Stephen
Abstract : As well as being one of the oldest and best known of all poetic forms, the sonnet is also one of the most widely travelled. Critical studies of the sonnet in English have traced its historical development from its Italian predecessors, through its domestication in Elizabethan England, to its remarkable popularity among modern British, Irish, and American poets. There is still much to learn, however, about the geography of the sonnet. This essay looks at some of the ways in which the sonnet has been shaped in places distant from its familiar European cultural domain: in Roy Campbell's South Africa, Allen Curnow's New Zealand, and Derek Walcott's St Lucia. It claims that, paradoxically, the intense compression of the sonnet form generates a powerful preoccupation with worldwide vision. It also proposes that the shape and size of the sonnet makes it an especially attractive form for poet-translators, and that the circulation of translations, imitations, and versions of sonnets greatly enhances the geographical mobility of the form. The essay concludes that some of the most innovative experiments with the sonnet form, by writers such as Don Paterson and Paul Muldoon, have been those concerned with latitude, and with the crossing of cultural and geographical boundaries.